2011
DOI: 10.1186/1471-230x-11-12
|View full text |Cite
|
Sign up to set email alerts
|

Modified mallampati classification as a clinical predictor of peroral esophagogastroduodenoscopy tolerance

Abstract: BackgroundUnsedated esophagogastroduodenoscopy (EGD) is simpler and safer than sedated EGD; however, approximately 40% of patients cannot tolerate it. Early identification of patients likely to poorly tolerate unsedated EGD is valuable for improving compliance. The modified Mallampati classification (MMC) has been used to evaluate difficult tracheal intubation and laryngoscope insertion. We tried to assess the efficacy of MMC to predict the tolerance of EGD in unsedated patients.MethodsTwo hundred patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…A study by Campo R et al indicated that having prior endoscopy can significantly affect the tolerance of examinations (5). Two studies conducted in Taiwan, which included respondents who had an upper endoscopy without sedation, found associations between negative experience with prior endoscopies and increased anxiety before the endoscopic examination as well as patient satisfaction (12,16). Similar results were obtained from a study conducted in Germany on patients who were included in the screening programme for colorectal cancer, where researchers tried to establish a link between the avoidance of examinations and previous bad experiences (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Campo R et al indicated that having prior endoscopy can significantly affect the tolerance of examinations (5). Two studies conducted in Taiwan, which included respondents who had an upper endoscopy without sedation, found associations between negative experience with prior endoscopies and increased anxiety before the endoscopic examination as well as patient satisfaction (12,16). Similar results were obtained from a study conducted in Germany on patients who were included in the screening programme for colorectal cancer, where researchers tried to establish a link between the avoidance of examinations and previous bad experiences (18).…”
Section: Discussionmentioning
confidence: 99%
“…The use of conscious sedation varies from country to country, continent to continent, and even in different endoscopy centres within the same country. The use of conscious sedation is associated with higher costs, an extension of the duration of the procedure, the need for the monitoring of vital functions and an increasing incidence of complications (10,12,14,16,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive physical exam with special attention to neck size (>16 cm in women, >17 cm in men) [13], nasal airflow (obtained by the patient occluding one nostril at a time), nasal septal deviation, jaw positioning (retrognathia), tonsil hypertrophy, narrow or high-arched hard palate, and Mallampati score (III or IV) (Fig. 1) [11,14].…”
Section: Clinical Evaluationmentioning
confidence: 99%